Evaluation of slope stability in earthen canal using GeoStudio simulation: a multi-parameter approach for the Khush Tepa Canal project, Afghanistan - Jahanzeb Rahimi; Bashir Ahmad Karimi; Nazir Ahmad Qani (Results in Engineering, 2025)
Canal slope failures are critical structural concerns that threaten human lives, the environment, and the economy as a whole. The stability of earthen channel slopes is a key consideration in the design and sustainability of large-scale irrigation systems, particularly in arid and semiarid regions. This study uses GeoStudio's SLOPE/W model to evaluate the slope stability of the Khush Tepa canal, employing a multi-parameter approach. Field and laboratory data were used to determine important geotechnical features, such as soil cohesiveness, internal friction angle, unit weight, and pore-water pressure. This research evaluated numerous scenarios, such as functional seepage, rapid drawdown situations and various bank loading conditions, to figure out their influence on the factor of safety (FoS). The SLOPE/W model was validated against the AACS empirical approach (2019), demonstrating reasonable agreement with the simulated results (14.1 % overestimation in steady state; 5.8 % underestimation in drawdown). The findings showed that slope stability is extremely susceptible to variations in hydraulic parameters and moisture content, with sudden drawdown scenarios showing the lowest FoS. The results highlight the importance of including thorough geotechnical evaluations and sophisticated numerical modeling in the design phase to ensure the lifespan and structural soundness of irrigation canals. Furthermore, the outcomes of the investigation indicate that the correlations and the use of simulation models perform well in assessing embankment slope stability. Consequently, the study provides valuable data for engineers and policymakers working to establish sustainable systems for managing water in comparable geotechnical environments.